Aerobic exercise program performed on a stationary bicycle associated to a photobiomodulation for knee osteoarthritis treatment: A placebo-controlled, double-blind, randomized, clinical trial and pilot study (Research, Society and Development, 2024)
Objective: Investigate the effects of photobiomodulation (PBMT) and an exercise program aerobic on pain, range of motion, mobility, functionality and quality of life of women with knee osteoarthritis (OA). 24 volunteers were included and randomized into 2 groups: Exercise and Placebo PBMT Group (EPPG) (n=12) and Exercise and Active PBMT Group (EAPG) (n=12). The aerobic exercise program was performed on a stationary bicycle, 2 times a week and PBMT was applied in the most affected lower limb. Visual Analogue Scale (VAS) of pain, Knee Injury and Osteoarthritis Outcome Score (KOOS), and Medical Outcomes Study 36-item Short Form Health Survey (SF-36) were used. In addition, Knee Flexion Range of Motion (ROM), 40m Fast-Paced Walk Test (40mFPWT), 9-Stair Climb Test (9-step SCT) and, 30s Chair Stand Test (30sCST). Results: The level of pain was significantly reduced for both groups after the intervention (EAPG p= 0.01; EPPG p= 0.01). Also, a significant increase in the variables measured by KOOS evaluation for both groups were seen after the treatment. An increase in functional capacity of SF-36 was observed only in the EAPG group (p= 0.004) in the revaluation compared to evaluation. For the evaluations of active flexion ROM, 40m Fast-Paced Walk, 9-Stair Climb and 30s Chair Stand Tests no differences were seen for both groups in the reevaluation. Conclusions: After 8 weeks, the aerobic exercise program (with or without PBM) was effective pain, symptoms, activities of daily living, function in sport and recreation, quality of life and general KOOS score in women with knee osteoarthritis (KOA).